On some Encyrtidae (Hymenoptera: Chalcidoidea) associated with gall-inducing psylloids, Phacopteron and Trioza species (Hemiptera: Phacopteronidae, Triozidae) in southern India - Hayat, Mohammad; Saleem, U. K. A.; Nasser, M. (Zootaxa, 2012)
Two new species, Ooencyrtus alrake Hayat, sp. nov. and Syrphophagus wayanadensis Hayat, sp. nov. (Hymenoptera: Chalcidoidea: Encyrtidae), are described from material collected in Kerala State (India) from Trioza jambolanae Crawford (Hemiptera: Psylloidea: Triozidae), a leaf gall-inducer on species of Syzygium (Myrtaceae). Two species, Psyllaephagus garuga S. Singh and P. phacopteron S. Singh, both recently described in S. Singh & K.P. Singh, (2011) from Dehra Dun, are recorded from Kerala from Phacopteron lentiginosum Buckton (Hemiptera: Psylloidea: Phacopteronidae) a leaf gall-inducer on Garuga pinnata Roxb. (Burseraceae). Some variation in the Kerala and Dehra Dun specimens of these two species is noted. It appears that this is the first record of Ooencyrtus Ashmead on psylloid hosts.